Βιβλιοκρισία: Caroline Walker Bynum, Dissimilar Similitudes. Devotional Objects in Late Medieval Europe, New York 2020 - ΓΙΑΝΤΣΗ-ΜΕΛΕΤΙΑΔΗ Νικολέττα; Γιολίνα ΓΙΩΤΑ-ΑΠΟΣΤΟΛΑΚΗ (Byzantina Symmeikta, 2022)
Βιβλιοκρισία: Caroline Walker Bynum, Dissimilar Similitudes. Devotional Objects in Late Medieval Europe, New York 2020